RESULTS OF EXPERIMENTAL RESEARCH COMPARING THE EFFICIENCY OF MARINE SAMPLERS IN RESEARCHING THE CONTENT OF MICROPLASTIC IN BOTTOM SEDIMENTS - V.O. Iemelianov; Ye.І. Nasiedkіn; T.S. Kukovska; N.O. Fedoronchuk; S.M. Dovbysh (Геологія і корисні копалини Світового океану)
The publication discusses one of the methodological aspects of microplastic research in bottom sediments with the involvement of a field experiment with the selection of natural matter by various means. Sampling was carried out within the western part of the Black Sea by specialists of the State Scientific Institution "MarGeoEcoCenter of the National Academy of Sciences of Ukraine" during research under the international project "Developing Optimal and Open Research Support for the Black Sea" in 2022. As a result of the performed field and laboratory work, new data were obtained, which allow us to conduct comparative characteristics of the quality of bottom sediment sampling for the presence of microplastics with such devices as a multicorer and a bottom scoop, and to find out the potential loss of actual material by one of the devices in comparison with another. This allows not only to improve the selection method and prevent the loss of actual material, but also to form the appropriate coefficients of quantitative conversion in the event that it is necessary to involve both options for obtaining samples of bottom sediments within the framework of one task. In general, the work carried out allows to gain important practical experience in the field of research of microplastics in the geological environment of sea basins.